Past, Present and Future: Perspectives on an Oral History of Intellectual Disability Nursing. (March 2023) - Doyle, Carmel; Griffiths, Colin; McAnelly, Su; Atherton, Helen; Cleary, Michelle; Fleming, Sandra; Gates, Bob; Keenan, Paul; Sutton, Paul
Thirty-one participants engaged in this oral history research study aimed at exploring the lived experience of intellectual disability nurses and healthcare assistants' knowledge of the trajectory of intellectual disability nursing over the last 30 years in the Republic of Ireland and England. This paper documents some of these experiences offering perspectives on intellectual disability nursing and what is important for the future. Findings from Ireland consider the nature of intellectual disability services and the registered nurse in intellectual disability. Findings from England focus on opportunities and restrictions in intellectual disability nursing, shared visions, the changing context within which work took place and also the internal and external supports that impacted their roles. It is evident that intellectual disability nurses must be responsive to the changing landscape of service provision and also the requirements for contemporary new roles to meet the changing needs of people with intellectual disabilities.